A Method for Alias Reduction in Cascaded Filter Banks - Schuller, Gerald; Edler, Bernd; Doser, Adele (9th IEEE DSP Workshop, 2000)
This paper shows a new way to reduce aliasing in crit- ically sampled cascaded filter bank structures. Un- like standard tree structured methods, which lead to many aliasing components in the final subbands, our approach reduces the effect by canceling aliasing ele- ments among subbands. Our interest lies in compres- sion applications where we can apply the scheme to obtain an unequal or non-uniform band splitting using uniform cosine modulated filter banks. In an example it is shown that a reduction in aliasing of over 40 dB compared to a traditional tree structured filter bank can be achieved.